Coastal Geomorphology of a Holocene Hurricane Deposit on a Pleistocene Marine Terrace from Isla Carmen (Baja California Sur, Mexico) - Markes E. Johnson; Jorge Ledesma-Vázquez; Rigoberto Guardado-France (Journal of Marine Science and Engineering, 2018)
This study reports the first example of major erosion from hurricanes degrading a rocky coastline anywhere around the Gulf of California, although other sources of evidence are well known regarding the effect of inland erosion due to catastrophic rainfall in the Southern Cape Region of the Baja California peninsula and farther north. The uplifted, 12-m terrace on the eastern shore of Isla del Carmen is the site of an unconsolidated coastal boulder deposit (CBD) consisting of large limestone blocks and boulders eroded from underlying Pliocene strata. The CBD stretches approximately 1.5 km in length, mostly set back 25 m from the lip of the terrace. The largest blocks of upturned limestone near the terrace edge are estimated to weigh between 5.8 and 28 metric tons. Waves impacting the rocky coast that peeled back slabs of horizontally-layered limestone at this spot are calculated to have been between 11.5 and 14 m in height. Analysis of sampled boulders from the CBD set back from the terrace edge by 25 m suggest that the average wave height responsible for moving those boulders was on the order of 4.3 m. Additional localities with exposed limestone shores, as well as other more common rock types of igneous origin have yet to be surveyed for this phenomenon elsewhere around the Gulf of California.